Information is Power: An Interventional Study on Parents of Children with Febrile Seizures - Deniz Özalp Kızılay; Asusinem Akyalçın Kırdök; Pelin Ertan; Senem Ayça; Mehmet Murat Demet; Muzaffer Polat (Galenos Yayinevi, 2017)
Aim: Febrile seizures (FS) cause great fear and panic in the families. The majority of parents think that they may lose their child during a seizure, and feel anxious about the possibility of seizures recurring in the future. We believe that educating the families with high levels of anxiety due to FS may help to reduce the level of anxiety. In this study, we aimed to determine the needs of parents regarding FS, and the effect of education on FS on the approach and anxiety of the parents. Materials and Methods: In our study, we interviewed the parents of 113 children who suffered from FS. We conducted a survey aiming at detailed detection of knowledge, attitudes, thoughts and concerns of the families about FS, and their approaches to fever and FS. We also performed Hospital Anxiety and Depression Scale and State-Trait Anxiety Inventory to determine the levels of anxiety and depression of the parents. Results: In this study, we found that parents were misinformed and had misbeliefs suggesting that FS damage the brain and cause epilepsy, that they are life-threatening and electroencephalography, magnetic resonance imaging and computed tomography scans of the brain are required. We also determined a significant lack of information about interventions during a seizure and thus, a high level of anxiety. Conclusion: We concluded that parents provided with sufficient information and given psychosocial support have their anxiety levels significantly reduced, making them better in first aid practices and reducing their requests for unnecessary preventive interventions.